The developmental course of salivary alpha-amylase and cortisol from 12 to 36 months: Relations with early poverty and later behavior problems. (February 2015) - Hill-Soderlund, Ashley L.; Holochwost, Steven J.; Willoughby, Michael T.; Granger, Douglas A.; Gariépy, Jean-Louis; Mills-Koonce, W. Roger; Cox, Martha J.
Highlights: We mapped the developmental trajectories of baseline salivary alpha-amylase (sAA) and cortisol from 12 to 36 months of age. The largest changes in both systems were seen in the second year of life, with sAA increasing and cortisol decreasing. Children residing in poor households exhibited lower initial levels of sAA, but not cortisol. Initial levels of sAA predicted higher levels of internalizing behaviors at 36 months and both initial levels of and total change in sAA predicted higher levels of externalizing behaviors at 36 months. Summary: This study examined the development of baseline autonomic nervous system (ANS) and hypothalamic–pituitary–adrenal (HPA) physiological activity from 12 to 36 months as well as antecedents (poverty) and consequents (behavior problems) of individual differences in physiological development. Children ( N  = 179; 50% poor; 56% African American; 52% male) provided saliva samples at 12, 18, 24, 30, and 36 months of age. Latent growth curve models indicated that nonlinear change was evident for both sAA and cortisol, with sAA increasing and cortisol decreasing with age. Children residing in poor households exhibited lower initial levels of sAA, but not cortisol. African-American children showed slightly smaller decreases in cortisol over time. Initial levels of sAA predicted higher levels of internalizing behaviors at 36 months and both initial levels of and total change in sAA predicted higher levels of externalizing behaviors at 36 months. There was no evidence that sAA or cortisol mediated the relationship between poverty and later behavior problems.